2010
DOI: 10.1111/j.1471-4159.2009.06489.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of glutamate receptors and phosphorylation of CREB are responsible for in vivoΔ9‐THC exposure‐impaired hippocampal synaptic plasticity

Abstract: J. Neurochem. (2010) 112, 691–702. Abstract Chronic use of marijuana impairs synaptic plasticity and cognitive function. However, the molecular mechanisms by which marijuana alters long‐term synaptic plasticity are largely unknown. Here, we show that repeated in vivo exposures to Δ9‐THC for 7 consecutive days significantly impaired hippocampal long‐term potentiation (LTP) of excitatory glutamatergic synaptic transmission. The Δ9‐THC exposure‐induced decrease in LTP was prevented by pharmacological inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 71 publications
8
67
0
1
Order By: Relevance
“…When THC was administered chronically for 7 days, but not after a single administration, Schaffer collateral-CA1 LTP generated by theta-burst stimulation or high-frequency stimulation in hippocampal slices was abolished [58]. A similar result was obtained after chronic THC in hippocampal perforant path LTP induced by theta-burst stimulation [59]. The blockade of LTP as the result of chronic exposure to THC persisted for 3 days after its last administration, and did not fully recover until 14 days of the last THC injection [58].…”
Section: Mechanisms Underlying Memory Modulation By the Endocannabinosupporting
confidence: 62%
“…When THC was administered chronically for 7 days, but not after a single administration, Schaffer collateral-CA1 LTP generated by theta-burst stimulation or high-frequency stimulation in hippocampal slices was abolished [58]. A similar result was obtained after chronic THC in hippocampal perforant path LTP induced by theta-burst stimulation [59]. The blockade of LTP as the result of chronic exposure to THC persisted for 3 days after its last administration, and did not fully recover until 14 days of the last THC injection [58].…”
Section: Mechanisms Underlying Memory Modulation By the Endocannabinosupporting
confidence: 62%
“…⌬ 9 -THC causes downregulation, internalization, and endocytosis of glutamate receptors or increases synaptic and astrocytic release of glutamate, thereby elevating extracellular glutamate levels (251,324). Interestingly, the reduced expression of glutamate transporters in ⌬ 9 -THC-exposed animals is attenuated by COX-2 inhibitors (138).…”
Section: Cnsmentioning
confidence: 99%
“…Cognitive impairments, apparently associated with alterations in synaptic transmission and functional expression of glutamate receptor subunits, may be observed with high doses of ⌬ 9 -THC (251,324,577). ⌬ 9 -THC causes downregulation, internalization, and endocytosis of glutamate receptors or increases synaptic and astrocytic release of glutamate, thereby elevating extracellular glutamate levels (251,324).…”
Section: Cnsmentioning
confidence: 99%
“…These findings suggest a direct relationship between the actions of cannabinoids on hippocampal processes and the ability to encode information into short-term memory Deadwyler and Hampson, 2008. Considerable evidence demonstrates that cannabinoid receptor agonists impair, whereas cannabinoid receptor antagonists improve, memory and plasticity (Ademark et al, 2009;Fan et al, 2010). However, recent studies suggest that the effects of cannabinoids on learning do not necessarily follow these simple patterns, particularly when emotional memory processes are involved.…”
Section: Cannabis Cannabinoids and Neuronal Plasticitymentioning
confidence: 92%
“…Fan et al (2010) found that repeated in vivo exposures to Δ9-THC for 7 consecutive days significantly impaired hippocampal LTP of excitatory glutamatergic synaptic transmission, and this decrease in LTP was prevented by pharmacological inhibition or deletion of the CB1 receptor. They showed that reduced expression and function of the GluR subunits and phosphorylation of cAMP response element-binding (CREB) may underlie the impaired long-term synaptic plasticity induced by repeated in vivo exposure to Δ9-THC.…”
Section: Cannabis Cannabinoids and Neuronal Plasticitymentioning
confidence: 99%